Phytochemical Constituents and Pharmacological Effects of Baeckea Frutescens: A Review - Abdul Wahid Suleman; Nurkhasanah Mahfudh; Nanik Sulistyani (Postgraduate, University of Mataram, 2025)
Baeckea frutescens is a medicinal species widely used in traditional practices and known for its rich phytochemical diversity, yet its pharmacological profile remains fragmented across multiple studies. This systematic review aims to integrate current evidence on the phytochemical constituents and pharmacological activities of B. frutescens, focusing on anti-inflammatory, antimicrobial, antioxidant, anticancer, wound-healing, and insecticidal effects. A literature evaluation was conducted using previously compiled research comprising 16 studies from China, Indonesia, Malaysia, and Southeast Asia, covering chemical isolation, essential oil analysis, in vitro assays, in vivo experiments, and computational approaches. The results indicate that B. frutescens contains meroterpenoids, phloroglucinol derivatives, flavonoids, phenolics, and terpenes that collectively contribute to significant modulation of NF-κB, MAPK, TLR4–MyD88, and COX-related pathways. Essential oils and polar extracts exhibit broad antimicrobial and antioxidant activities, while cytotoxic and wound-healing assays demonstrate promising therapeutic potential. Insecticidal studies further highlight ecological relevance through antifeedant and repellent properties. Overall, the review confirms B. frutescens as a pharmacologically versatile species with strong prospects for drug discovery and functional applications. However, further mechanistic and in vivo investigations are needed to strengthen its translational value.